Neurovascular coupling and functional neuroimaging in epilepsy - Becker Junior,Valesio (2009)
INTRODUCTION: The neural regulation of the microcirculation is done by the functional neurovascular unit that is composed of vascular, astroglial and neuronal cells. The neurovascular unit represents the interface between the Central Nervous System and the Vascular System. OBJECTIVE: This paper reviews the literature on functional neuroimaging with a particular focus on the mechanisms of the neurovascular coupling. CONCLUSIONS: Functional neuroimaging techniques as functional MRI, SPECT and PET distinguish metabolic and physiological processes underlying normal and abnormal events, based on neurovascular coupling. Although these techniques still have limitations in temporal and spatial resolution, they have considerably reduced the need for intracranial electrodes or invasive functional tests in the presurgical evaluation for intractable epilepsy. Recently, new techniques as optical approaches (measurement of intrinsic optical signals and near infrared spectroscopy) have increased both temporal and spatial resolutions. The use of such techniques in animal models has yielded experimental evidence for a neurovascular coupling in normal and epileptic conditions.